Effect of warfarin on cell kinetics, epithelial morphology and tumour incidence in induced colorectal cancer in the rat. Issue 8 (August 1985) - Goeting, N; Trotter, G A; Cooke, T; Kirkham, N; Taylor, I
Abstract : The effect of low dose warfarin and high dose warfarin on epithelial cell kinetics (as determined by stathmokinetic techniques), and preneoplastic morphological changes was studied during azoxymethane induced carcinogenesis in the rat. Warfarin, at either low or high dose, had no effect on crypt cell production rate (CCPR) at any time interval whereas tumour incidence in both low dose warfarin and high dose warfarin groups was significantly reduced. Morphological changes were observed using scanning electron microscopy, which by conventional histology were shown to be adenoma precursors. In the control group the number of microadenomas increased with time after starting azoxymethane. In warfarin treated animals, the number of microadenomas also increased with time, but the actual incidence was reduced when compared with controls. These results suggest that the effects of warfarin on tumour development is unrelated to its anticoagulant effect, because increased dose did not result in greater tumour reduction. Furthermore, there was no overall change in CCPR when warfarin was administered. Warfarin may exert a specific effect, by preventing neoplastic change in cells which have undergone morphologically undetectable changes associated with early carcinogenesis.